On the Historicity of Acts: Comparing Acts 9.23–5 with 2 Corinthians 11.32–3 - Harding, Mark (New Testament studies, 1993)
The death of Colin Hemer in 1987 has deprived the fellowship of New Testament scholars of one who, like his late mentor F. F. Bruce, was able to bring to bear on the study of the text of the New Testament the insights and discipline of one trained in the Classics. Hemer's posthumously published The Book of Acts in the Setting of Hellenistic History is an attempt on a large scale to argue the case for the historicity of Acts with respect to attention to matters of detail, and, as a consequence, the trustworthiness of its author. Luke the historian, contends Hemer, deserves to be judged according to the historiographical conventions of his day, the conventions of a venerable historiographical heritage whose great exemplar in the Hellenistic era was Polybius. Hemer's bringing of a vast collection of epigraphical and archaeological evidence to bear on the question of Lukan historicity should shake the presuppositions and conclusions of the sceptical and help NT scholars to appreciate both Lukan accuracy and Acts' ‘topicality’.